Mulla Sadra's Realism on The Principle of Ittihad al-'Aqil wa al-Ma'qul: A Response to Modern Realism - Walid, Kholid Al (FIKRAH, 2023)
This article attempts to show Mulla Sadra’s model of realism by tracing it through his philosophical principles, especially the principle of Ittihad 'Aqil wa Ma'qul (subject-object unity). Furthermore, the study of the Sadra realism model, which is based on the principle of Ittihad 'Aqil wa Ma'qul, is presented to respond to fundamental epistemic-ontological issues, namely the relationship between the subject’s consciousness and external objects, in order to strengthen belief in the nature and existence of external reality, which is independent of contamination of the subject's mental decisions (mind-independent reality). How does the subject's consciousness relate to external objects? This problem is still an anxiety and has not been resolved by modern philosophers who focus on the discourse of perception, giving rise to various schools of realism, which are represented by two major schools: direct realism and indirect realism. By overcoming these epistemic problems, ultimately, this effort leads to the confirmation of Mulla Sadra's more original and comprehensive model of realism. This paper is attempted using a critical-analytical method, namely analyzing Mulla Sadra's philosophical ideas on the Ittihad 'Aqil wa Ma'qul principles and the views of modern realism by focusing on the issue of perception. The conclusions drawn from the results of the analysis of the Ittihad 'Aqil wa Ma'qul were used as a basis for responding to modern realism as well as an affirmation of Mulla Sadra's style of realism.